2015
DOI: 10.4269/ajtmh.15-0166
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Ventilation and Early Diagnosis on Tuberculosis Transmission in Brazilian Prisons

Abstract: Abstract. Prisoners have among the highest incidence of tuberculosis (TB) globally. However, the contribution of the prison environment on transmission is not well understood and structural characteristics have received little attention as effective epidemiological interventions in TB control. We evaluated architectural characteristics and estimated ventilation rates in 141 cells in three prisons in central west Brazil using steady-state exhaled carbon dioxide (CO 2 ) levels. We used a modified Wells-Riley equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 31 publications
(29 reference statements)
1
53
0
3
Order By: Relevance
“…A recent study demonstrated high rates of nonadherence to treatment among prison prisoners in Brazil, underscoring the need to ensure that prisoners complete treatment to prevent transmission within and outside prisons ( 15 ). In addition to improving access to TB diagnosis and treatment within prisons, addressing rising incarceration rates and improving living condtions that favor transmission in prisons may be critical to combat TB among prisoners ( 16 ). …”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated high rates of nonadherence to treatment among prison prisoners in Brazil, underscoring the need to ensure that prisoners complete treatment to prevent transmission within and outside prisons ( 15 ). In addition to improving access to TB diagnosis and treatment within prisons, addressing rising incarceration rates and improving living condtions that favor transmission in prisons may be critical to combat TB among prisoners ( 16 ). …”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated high rates of nonadherence to treatment among prison prisoners in Brazil, underscoring the need to ensure that prisoners complete treatment to prevent transmission within and outside prisons (15). In addition to improving access to TB diagnosis and treatment within prisons, addressing rising incarceration rates and improving living condtions that favor transmission in prisons may be critical to combat TB among prisoners (16). Ronnie Henry…”
Section: Discussionmentioning
confidence: 99%
“…A study comprising 59% of inmates in 12 prisons in the state throughout 2013 revealed prevalence and incidence rates per 100,000 prisoners of 951 and 1839, respectively 14 , with the latter being similar to the 830.6 rate found in a sample of 2237 prisoners in São Paulo in 2008 20 In 2014, Mato Grosso do Sul had the highest incarceration rate (568.9 per 100,000 population) and the fourth highest prison occupancy rate (216%), ranking 11th among the 28 Brazilian state-level administrative divisions in number of prisoners 19 . Overcrowding, compounded by poorly ventilated cells deprived of sunlight, potentiates the likelihood of bacillus transmission 6,7,9 . In 2014, Mato Grosso do Sul had the highest incarceration rate in the country (568.9 per 100,000 residents) and the fourthhighest occupancy rate (216%), ranking 11 th among the 28 Brazilian state-level administrative units in terms of number of inmates 19 .…”
Section: Discussionmentioning
confidence: 99%
“…In the midwestern State of Mato Grosso do Sul, the risk of pulmonary tuberculosis (PTB) is 25.3 times higher in prison population than in the general population 5 . In the prison population, a number of vulnerabilities-overcrowding, late detection of the disease, poorly ventilated facilities, malnutrition, inadequate control of cases and contacts, high HIV prevalence, alcohol, and illicit drugs-are likely to interact, facilitating infection with Mycobacterium tuberculosis and progression of disease 2,[6][7][8][9] . In addition, a high turnover rate within and across prisons 10 , poor access to healthcare, and low adherence to treatment contribute to delayed diagnosis 2,7 , maintenance of the transmission chain, and emergence of multiresistant strains 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation